Understanding the Basic Concepts Of Early Childhood Education in Islamic Education - A.Ghani, Sulhan Hamid (Jurnal Paradigma, 2021)
The nature of childrenhas been always an interesting phenomenon in human life in various societies from ancient times to modern times, therefore children have been tried to be understood both physically and spiritually, both by the general public and experts in various fields. Psychologists have tried to investigate the nature of children; in line with that, this paper attempts to conduct a research on the basic concepts of early childhood education in Islamic education. This study tries to uncover the basics of early childhood education according to the concept of Islamic teachings, however it does not rule out the opinions of experts in the field of early childhood education. Based on the analysis of the research, it can be concluded that: psychologists in understanding the nature of children and their development gave rise to 4 theories, those are: nativist, naturalist, empirical and convergent, each of which had an impact on the world of education, especially early childhood education. Early childhood needs attention in growth and development; and basically, there are 6 aspects which, if those are implemented in the learning process, require an understanding of basic competencies for early childhood education. Islam places early childhood as something very crucial, so that early childhood education must receive adequate attention and it can beunderstood that with the rights of early childhood according to Islamic education.